Flocculation behaviour of colloidal suspension by use of inorganic and polymer flocculants in powder form - Kadooka, Hiroto; Kiso, Yukari; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2013)
Flocculation is a typical process which does not progress stoichiometrically. Reproducibility of flocculation with polymer flocculant depends strongly on the amount of additive, the manner of addition and mixing intensity. It has been found that a dry powder flocculant mixture composed of inorganic flocculant, polymer flocculant and flocculation aid shows high reproducibility of turbidity removal as long as it contains an adequate amount of flocculation aid. The flocculation aid helps the dispersion of the polymer powder into a suspension. It has been reported that the morphology and the amount of adsorbed ionic polymer flocculant (polyelectrolyte) on suspended particle depend on the ionic strength of suspension. The flocculation process and the turbidity removal of colloidal suspension are mainly determined by the morphology and the adsorped amount of polymer on a solid surface. In this study, in order to investigate the effect of dosage of inorganic and ionic　polymer flocculants on turbidity removal, a time course of optical density of PMMA suspension was measured and the floc morphology was observed. The following results were obtained. 1. An optimum dosage of ionic polymer flocculant depends on dosages of inorganic flocculant and flocculation aid. 2. As dosage of inorganic flocculant increases, the optimum dosage of ionic polymer flocculant increases for better turbidity removal. A flocculation mechanism of PMMA is discussed, and a procedure for determining optimum composition of a composite dry powder flocculant for turbidity removal is proposed.